2017
DOI: 10.1021/acsbiomaterials.6b00669
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Trends in Artificial Silk Spinning: A Systematic Review

Abstract: More than 400 million years of natural selection acting throughout the arthropoda has resulted in highly specialized and energetically efficient processes to produce protein-based fibers with properties that are a source of inspiration for all. As a result, for over 80 years researchers have been inspired by natural silk production in their attempts to spin artificial silks. While significant progress has been made, with fibers now regularly outperforming silkworm silks, surpassing the properties of superior s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
242
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(251 citation statements)
references
References 132 publications
(318 reference statements)
3
242
0
Order By: Relevance
“…Silk fibers produced by silkworms and spiders possess exceptional mechanical properties that exceeds many synthetic polymers . Numerous efforts have been devoted to mimicking the fiber production process by the insects using regenerated silk solutions . However, the as‐spun regenerated silk fibers (RSF) are usually brittle and requires complex post‐treatment (e.g., dehydration and crystallization processes) to yield useful fibers .…”
Section: Multiscale Manufacturingmentioning
confidence: 99%
“…Silk fibers produced by silkworms and spiders possess exceptional mechanical properties that exceeds many synthetic polymers . Numerous efforts have been devoted to mimicking the fiber production process by the insects using regenerated silk solutions . However, the as‐spun regenerated silk fibers (RSF) are usually brittle and requires complex post‐treatment (e.g., dehydration and crystallization processes) to yield useful fibers .…”
Section: Multiscale Manufacturingmentioning
confidence: 99%
“…The results indicated that the highly condensed BSA network crosslinked by GA plays an important role in increasing the fibers' strength and toughness. Notably, this outstanding toughness is already at the same level as the spider dragline silk and is even superior to that of many recombinant spider silks and regenerated silkworm fibers . Meanwhile, the Young's moduli of the fibers are ≈3 GPa (Figure S20, Supporting Information), indicating the preserved stiffness in the BSA fibers.…”
Section: Resultsmentioning
confidence: 90%
“…Meanwhile, the breaking strength was approximately 130 MPa and the toughness increased to approximately 143 MJ m −3 (Figure B). The present toughness of GBF is in the same level as the spider dragline silk (approximately 150 MJ m −3 ) and is even superior to that of many recombinant spider silks and regenerated silkworm fibers . Notably, the toughness of the double GA‐crosslinked GBF was at least 70 times higher than the PBF and one‐time GA crosslinked GBF.…”
Section: Figurementioning
confidence: 80%